التناغم الرمزي والدلالي في الشعر الصوفي موازنة سيميائية في ثلاثة نصوص من الأدب العربي والفارسي والكردي - الله, شاهو سعيد فتح (Sulaimani Journal for Humanities, 2007)
This research, entitled: "The symbolical and significant Coherence of the Sufist Poetry: A Semiotic Comparison of Three Poems in Arabic, Persian and Kurdish Literature", is an attempt to study sufist poetry from two aspects: first is the theoretical aspect about the semiotic and symbolical method, and the second is the practical and comparative study in three texts of three outstanding poets: Ibn Arabi, Hafiz Al-Shirazi and Mahwi. The paper comprises the following: A theoretical introduction chapter deals with the problem and critical method of the research. The first, second and third chapters are practical approaches and touch upon the texts. The fourth chapter compares the three texts to one another.